An internet-based course on neural networks - Rodrigues, C. (2013)
Web based instruction is increasingly attracting the interest of Universities. In this paper, an Internet based course on neural networks, developed in the University of Algarve, is discussed. A special attention is given to techniques of student self-assessment. A structure of knowledge, to enable the automatic creation of on-line courses, is proposed.